Analisis Kinerja Keuangan Dengan Time Series Pada Perusahaan Pulp Dan Kertas Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2018-2020 - Magdalena, Firensia; Ratih, Suklimah (Jurnal Etnik: Ekonomi-Teknik, 2022)
Financial performance in general is a business carried out by every companies to measure and judge every success achieved in make a profit. One of the measuring tools to determine the financial position and position The success of a company is with the financial ratio. This research aimed to knowing financial performance with a Time Series on Pulp and paper Company Registered Paper Exchange 2018-2020". This study uses secondary data as many as 9 pulp and paper listed on the Indonesia Stock Exchange. The election until using purposive sampling method, so that the research sample is found as much as 7 companies. The period used by the researcher was ad from 2018-2020. The result of the research conclusion research based on the calculation of the profitability ratio. The pulp and paper companies that are in good circumstances from the profitability ratio, exviewed from gross profit margin, net profit margin, return on eqity and return on assets from 2018-2020 is PT. Fajar Surya Wisesa Tbk (FASW). The liquidity ratio that is seen at the cash ratio, current ratio and the quick ratio is PT. Indah Kiat Pulp & Paper Tbk (INKP). The ratio of solvency in the debt to equity ratio of solvency and debt to asset ratio is PT. Suparma Tbk (SPMA). The ratio of activity on receivable turnover ratio, inventory turnover, fixed asset turnover, total reset turnover and turnover capital is PT. Kedawung Setia Industrial Tbk (KDSI).